The Process of Social Interaction in Forming and Maintaining the Symbolic Meaning of "Tedong Bonga" in the Toraja Society - Iskandar, Abdul Malik; Hemma, Teobaldus; Ashar, Muhammad; Kasim, Hasanudin; Harifuddin, Harifuddin; Mohamed, Sheik (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2025)
This study aims to describe the process of social interaction in forming and maintaining the symbolic meaning of Tedong Bonga in the Tanah Toraja Society . The study uses an explanatory case study approach and uses a purposive sampling technique with 1 key informant, namely a traditional figure and 7 supporting informants, youth or students from Tana Toraja. Data collection in this study was carried out through interviews, observations and documentation. The data analysis technique used was qualitative. This study uses triangulation to obtain data validity. Based on the results of the study, it can be concluded that tedong bonga is a cultural symbol that has spiritual, social, and economic meaning for the Toraja Society . This meaning is formed and maintained through social interaction in the Rambu Solo' procession, activities at the animal market, and informal education by traditional elders. In addition to being a symbol of respect for ancestors, tedong bonga also reflects the social status of the family. The role of traditional elders is very important in passing on these values ​​to the younger generation so that they remain sustainable amidst changing times.